THE PLIOCENE DEPOSITS IN THE CENTRAL-EASTERN VALDELSA BASIN (FLORENCE, ITALY), REVISED THROUGH FACIES ANALYSIS AND UNCONFORMITY-BOUNDED STRATIGRAPHIC UNITS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
The Valdelsa Basin is one of the widest post-collisional basins developed in central Tuscany (Italy) since the late Miocene. More than 2,000 m of upper Miocene-Quaternary deposits fill the basin and1,000 of which, ascribed to the Pliocene, crop out extensively. In previous studies these deposits have been included in poorly defined lithostratigraphic schemes, and also a detailed chronologic calibration via biostratigraphic analysis has produced few results due to the paucity of biomarkers. In this study the Pliocene deposits have been subdividedinto eleven lithofacies associations, in turn included in five unconformity-bounded stratigraphic units (synthems) spanning in age from the uppermost Zanclean to most part of Piacenzian. Lithofacies associations, defined as the recurring vertical alternance of several basic lithofacies, are in fact recognized based on both the lithologic features and the sedimentary/bio-(marine to continental molluscs) facies content which formedin specific environments. Several depositional systems activated in the basin, from alluvial to fluvio-deltaic to paralic and inner shelf systems, in response to change of sediment supply and accommodation space. The Pliocene paleogeography of the portion of the basin considered in this study was characterized by the occurrence of a structural high that separated two distinctdepositional areas in theearly stage of the basin fill. A marine (delta front to inner shelf) area developed in the central part (Certaldo-Castelfiorentino area), while an alluvial plain was forming eastward (in the S. Casciano area). During the Piacenzian the basin was characterized by the progressive filling of a shallow marine area (central part) due to the southwestward progradation of fluvio deltaic systems.